Investigating the relationship between anthropometric indicators of the mother during pregnancy with the weight, height, and head circumference of the infant at birth: A mother-infant cohort study - Leila Asadi; Zahra Mohebbi-Dehnavi; Razieh Sadat Tabatabaei; Ali Dadbinpour; Mahmood Vakili Ghasem Abad (Journal of Education and Health Promotion)
BACKGROUND: The growth and development of the fetus inside the womb depends on several factors, including the weight gain of the mother during pregnancy. The aim of the current research is to determine the relationship between anthropometric indicators of the mother during pregnancy and the weight, height, and head circumference of the infant at birth. MATERIALS AND METHODS: The present study is a Historical cohort study that was conducted on 1623 pregnant mothers from the beginning of pregnancy to delivery by census method in 4 reference and specialized gynecology and obstetrics hospitals affiliated to Shahid Sadougi University of Medical Sciences in Yazd from 2016 to 2021. The tools used were the questionnaires approved by the Ministry of Health and the Research Council of the University to conduct the mother-infant cohort. Data analysis was performed with SPSS Software Version 22 with analytical statistical tests. RESULTS: The baby’s weight had a significant negative relationship with the mother’s weight and the mother’s body mass index at the beginning of pregnancy. The baby’s height had a significant positive difference with the body mass index at the beginning of pregnancy. The baby’s head circumference had a positive and significant relationship with the mother’s weight in the third trimester of pregnancy. CONCLUSION: According to the results of the study and the importance of the health of the mother during pregnancy due to the effect on the health of the fetus, it is recommended to monitor the weight of mothers more sensitively from before pregnancy to the end of pregnancy.